1991
DOI: 10.1111/j.1476-5381.1991.tb12237.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence for the possible involvement of repetitive action potentials in facilitation by GABA of catecholamine secretion in bovine adrenal chromaffin cells

Abstract: γ‐Aminobutyric acid (GABA) evokes catecholamine (CA) secretion and enhances the stimulation‐evoked CA secretion via facilitation of Ca2+ entry in a Cl−‐dependent manner. The present study was designed to investigate further the ionic mechanism of modulation by GABA of CA secretion from adrenal medulla, using a primary culture of bovine chromaffin cells. Tetrodotoxin (TTX), a voltage‐sensitive Na+ channel blocker, reduced GABA‐evoked CA secretion. Inhibition of the sodium pump by ouabain or removal of extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Consistent with these observations, blockade of NKCC1 with bumetanide significantly shifted E Cl , as measured by changes in [Ca 2ϩ ] i . As discussed above, there is still considerable debate about whether activation of GABA A receptors in chromaffin cells inhibits the excitation produced by the physiological activator of chromaffin cells, ACh (Fujimoto et al 1987;Kataoka et al 1986;Kitayama et al 1990cKitayama et al , 1991. Our results suggest that activation of GABA A receptors in chromaffin cells is excitatory under all conditions.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Consistent with these observations, blockade of NKCC1 with bumetanide significantly shifted E Cl , as measured by changes in [Ca 2ϩ ] i . As discussed above, there is still considerable debate about whether activation of GABA A receptors in chromaffin cells inhibits the excitation produced by the physiological activator of chromaffin cells, ACh (Fujimoto et al 1987;Kataoka et al 1986;Kitayama et al 1990cKitayama et al , 1991. Our results suggest that activation of GABA A receptors in chromaffin cells is excitatory under all conditions.…”
Section: Introductionsupporting
confidence: 53%
“…In some cells, activation of GABA A receptors is depolarizing but is still inhibitory (Zhang and Jackson 1993). In chromaffin cells, there is considerable controversy whether GABA can inhibit responses to high K ϩ or ACh, even though GABA itself is excitatory (Fujimoto et al 1987;Kataoka et al 1986;Kitayama et al 1990cKitayama et al , 1991. To address this issue, we examined elevations in [Ca 2ϩ ] i in response to ACh, in the presence and absence of muscimol, to determine whether activation of GABA A receptors would inhibit the response to ACh.…”
Section: Co-activation Of Ach and Gaba A Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that GABA and acetylcholine are colocalized in the same nerve fibers and are released from them. Previous physiological study showed that GABA induced release of catecholamines from the chromaffin cells [1,[14][15][16], and that the GABA-induced secretory response is a consequence of the Ca 2+ influx through voltage-sensitive Ca 2+ channels in a Cl -depending manner [18,19]. Furthermore, it is generally accepted that acetylcholine stimulates release of catecholamine from the chromaffin cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, GABA depolarizes rodent sympathetic ganglia [42,43]. Application of GABA to bovine adrenal chromaffin cells activates action potentials [44] and increases [Ca2+]j [45,46], GABA-evoked repetitive action potentials are thought to facilitate catecholamine secretion from chro maffin cells by elevating cytosolic Ca2+ levels [47], Simi larly, the excitatory action of GABA on GT1-7 cells is probably responsible for the GABA-induced increase of GnRH secretion from these cells [12] and may explain the stimulatory actions of GABA on GnRH release from hypothalamic slices [7], Activation of a bicuculline-insensitive GABAa receptor has also been reported to stimulate LH release from female rat pituitary cells. This effect was mimicked by the selective GABAa receptor agonist mus cimol and was inhibited by voltage-activated Ca2+ chan nel blockers [48].…”
Section: Physiological Implications O F Gaba1 Receptor-mediated Excimentioning
confidence: 99%